Application of Soft Computing Techniques in Global Software Development: state-of-the-art Review - Iftikhar, Asim; Musa, Shahrulniza; Alam, Muhammad; Mohd Suâ€™ud, Mazliham; Mubashir Ali, Syed (International Journal of Engineering and Technology, 2018)
Developing Software through a globally distributed team is a modern trend, which is not only cost effective but also yields best project results mitigating risk and increasing return on investment. This is easily achieved by ensuring through put in production is maintained at all times irrespective of the clock time and geographical boundaries. This shift of phenomenon is happening across the board as more and more companies use this as a strategic tool. Modern day technology makes this all possible, without compromising quality, coding practices and project management techniques. In this paper we have researched several papers (2008 to 2018) and understood the data for soft computing to provide a strong basis for future directionsÂ Â